Interactions between ants, herbivorous insects and bracken (Pteridium aquilinum), a fern with extrafloral nectaries - Rashbrook, Vanessa Karin (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1989)
Bracken (Pteridium aquilinum) is a cosmopolitan species of fern which possesses extrafloral nectaries. A survey of the arthropod fauna associated with the plant throughout its range in South Africa identified the most widespread and damaging bracken herbivores and those species most likely to be influenced by ants visiting the extrafloral nectaries. Seventeen herbivorous arthropods were found to be definitely feeding on bracken and a further thirteen species with a less certain status were recorded. In addition, several species of ants were observed on the fronds and feeding at the extrafloral nectarie. On the basis of their widespread distribution and abundance, four bracken herbivores emerged as being particularly detrimental to the plant in South Africa. They were an eriophyid gall mite, a leafhopper and two moths. The biology of the two lepidopterans, Appana cinisigna and Panotima sp., suggested that they were potentially vulnerable to ants at various stages of their life histories. Laboratory experiments were undertaken to observe ant-lepidopteran interactions under controlled conditions. The ant Crematogaster peringueyi rapidly removed exposed A. cini igna eggs, but did not appear to regard Panotima eggs as food items. Small instar larvae of both species proved vulnerable, but the larger larvae appeared capable of escaping ant predation. Ant exclusion experiments in the field, using natural and artificially augmented ant densities, were carried out at two sites near Grahamstown. The dominant ant species was C. peringueyi. Neither the numbers of lepidopterans nor levels of herbivory were significantly reduced by the presence of ants . Despite the implications of the laboratory tests, the results of these field experiments did not support the hypothesis that ants which visit bracken extrafloral nectaries benefit the plant. Ant-bracken field studies on other continents also reported no significant ant-related effects, though marginal reductions in the abundance of certain herbivores have been noted at one site in the U.K. Since ant protection does not appear to be an inevitable consequence of having extrafloral nectaries, their value to bracken is in some doubt. The most likely situation where effective protection will occur is when high densities of vulnerable herbivores are preyed upon by large numbers of aggressive ants. However, even under these conditions, enhancement of plant fitness is not inevitable. This raises the question of why extrafloral nectaries have been retained in a plant that is as successful and widespread as bracken.
Keywords: Arthropod pests -- South Africa; Ants -- South Africa; Ferns -- South Africa